Effects of Product Quality, Price, Brand Image, and Brand Awareness on Pesticide Purchase Decisions Among Horticulture Farmers in Malang Raya - Hijriati Nur Sangadah; Arif Yustian Maulana Noor; Abdul Wahib Muhaimin (Agriculture Socio-Economic Department, Faculty of Agriculture, Brawijaya University, 2025)
Background and purpose – The increasing diversity of pesticide brands requires farmers to make purchasing decisions based on both functional product attributes and brand-related factors. This study aims to analyze the influence of product quality, price, brand image, and brand awareness on the purchasing decisions of horticultural farmers in Malang Raya. Methodology – The study employed a quantitative approach using survey data from 122 horticultural farmers across eight districts. The purchasing decision variable was analyzed using logistic regression. Findings – The results show that product quality and price have a positive and significant effect on purchasing decisions, indicating that functional attributes remain the dominant drivers of farmer product choice. In contrast, brand image and brand awareness exhibit no significant influence, suggesting that symbolic brand factors play a limited role in this market segment. Implications – The findings highlight the importance of strengthening technical product performance and developing competitive pricing strategies for companies seeking to increase market penetration among horticultural farmers. The study also provides empirical insight for policymakers and agribusiness stakeholders to refine extension and marketing strategies. Originality – This paper offers a focused empirical assessment of the determinants of pesticide purchasing decisions in horticultural production systems, integrating both functional and brand-related variables within a logistic regression framework, which remains limited in existing local agribusiness research. Keywords: brand awareness, brand image, consumer behavior, price, quality product